The hidden cost of digital learning: a cross-sectional study assessing the prevalence of computer vision syndrome (CVS) among medical students in Jordan - Hazim Alkousheh; Yara Alkousheh; Rana Qawaqzeh; Layan Al Juneidi; Lina Al-Zerikat; Ayat Hussain; Motasem Al-latayfeh (BMJ Open)
Objective Increased screen time has resulted in widespread computer vision syndrome (CVS) in the digital era. Medical students, who rely heavily on digital screens, are particularly at risk. Our study aims to evaluate the prevalence of CVS among Jordanian medical students, which is a gap in existing knowledge.Design Cross-sectional studySetting National multicentre study conducted across six universities in Jordan.Participants Medical students from first to sixth year.Primary and secondary outcome measures Primary outcome: Prevalence of CVS among medical students in Jordan.Secondary outcomes: Identification of risk factors associated with CVS, assessment of the correlation between screen time and the severity of CVS symptoms.Results The prevalence of CVS among medical students was 56.3%. Among the 833 participants, 543 were females (65.2%) and 290 were males (34.8%). The CVS group reported a median of five symptoms, whereas two symptoms were reported in the non-CVS group (p<0.001). Compared with males, females reported significantly more symptoms (p<0.001). Dry eyes (26.3%) and headaches (25.9%) were the most reported symptoms. Continuous screen use was associated with CVS group status (p=0.008). Moderate positive correlations were found between the number of symptoms and the frequency of monthly symptom attacks and between the duration and frequency of symptom attacks (p<0.001).Conclusion Our study found a 56.3% prevalence of CVS among Jordanian medical students, with over 80% having ocular and extraocular symptoms. Symptoms, attack duration and frequency were higher, especially in females, highlighting the need for preventive measures and increased awareness about prolonged screen use.